2021
DOI: 10.1155/2021/5541522
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the DWT-PCA/SVD Recognition Algorithm on Reconstructed Frontal Face Images

Abstract: The face is the second most important biometric part of the human body, next to the finger print. Recognition of face image with partial occlusion (half image) is an intractable exercise as occlusions affect the performance of the recognition module. To this end, occluded images are sometimes reconstructed or completed with some imputation mechanism before recognition. This study assessed the performance of the principal component analysis and singular value decomposition algorithm using discrete wavelet trans… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 9 publications
1
3
0
Order By: Relevance
“…From the numerical results, it can be concluded that when varying expressions are the underlying constraints, left reconstructed face images have relatively higher average recognition rate as compared to the right reconstructed face images using the DWT-PCA/SVD recognition algorithm. This finding is consistent with those of Singh and Nandi [11], and Asiedu et al [8,15] with the exception that their study focused on single constraints. The relatively lower average recognition rates of the DWT-PCA/SVD algorithm found in this study reflect the use of multiple constraints (partial occlusion and varying expressions).…”
Section: Conclusion and Recommendationsupporting
confidence: 92%
See 1 more Smart Citation
“…From the numerical results, it can be concluded that when varying expressions are the underlying constraints, left reconstructed face images have relatively higher average recognition rate as compared to the right reconstructed face images using the DWT-PCA/SVD recognition algorithm. This finding is consistent with those of Singh and Nandi [11], and Asiedu et al [8,15] with the exception that their study focused on single constraints. The relatively lower average recognition rates of the DWT-PCA/SVD algorithm found in this study reflect the use of multiple constraints (partial occlusion and varying expressions).…”
Section: Conclusion and Recommendationsupporting
confidence: 92%
“…Asiedu et al [15] assessed the performance of Principal Component Analysis and Singular Value Decomposition algorithm using Discrete Wavelet Transform (DWT-PCA/SVD) as a preprocessing mechanism on reconstructed face image database. The reconstruction of the half-face images was done leveraging on the property of bilateral symmetry of frontal faces.…”
Section: Introductionmentioning
confidence: 99%
“…For this reason, these methods are also called imprecise methods because random mechanisms have a significant impact on their structure [29]. Among the most important and widely used approaches, we can mention the genetic algorithm [30], differential evolution algorithm [31], particle swarm algorithm [32], ant colony algorithm [33], honey bee algorithm [34], and... which are widely used in various industries today In research [35], a face recognition algorithm based on wavelet transform and compression coefficient value is presented. The classification method is based on sparse representation (SRC) and is done by comparing the residual errors between test samples and reconstruction samples.…”
Section: -Related Workmentioning
confidence: 99%
“…The most influential and widely used approaches include genetic algorithms [29], differential evolution algorithms [30], particle swarm algorithms [31], ant colony algorithms [32], honey bee algorithms [33], used in various industries today. Asiedu et al [34] presented a face recognition algorithm based on wavelet transforms and compression coefficient values. Based on sparse representation (SRC), the classification method compares residual errors between test samples and reconstruction samples.…”
Section: Related Workmentioning
confidence: 99%